CHALLENGES OF CRIMINAL INVESTIGATION CYBER CRIME - Hartono, Wandi; Muhardi, Dekky; Akhiruddin, Ahmad; Purba, Desi Valentianna Br; Asa, Pandu; DM, Yusuf (Awang Long Law Review, 2024)
The investigation process still has many cases of cybercrime that are stalled due to the limited equipment owned by the Police, for example if there is a complaint or report from the public regarding the occurrence of cybercrime, the reporter reports the incident to the local Police, which usually does not have special equipment to examine complaints or reports from the public, so the Police must coordinate with the Resort Police, which if its equipment is still inadequate, must transfer the complaint or report to the Regional Police level which certainly has adequate equipment to handle cybercrime cases, this is an obstacle in the investigation in the internal sector. While for external factors themselves, there are various obstacles faced by investigators.The research that the author will conduct is normative, namely research that is based on applicable legal principles.. The conclusion isAfter understanding the regulation of investigation of cybercrime cases regulated in the Law on Information and Electronic Transactions, it can be concluded that the investigation process is carried out by a team of investigators from the Republic of Indonesia National Police who can be assisted by people who are experts in certain fields related to the case that is under investigation if needed in solving a case by maintaining privacy, data authenticity, and not disrupting public services or public facilities. Searches and/or seizures of electronic systems related to suspected criminal acts must be carried out with the permission of the local District Court.